Development of Autoimmune‐Mediated β Cell Failure After Total Pancreatectomy With Autologous Islet Transplantation. Issue 7 (12th March 2015) - Bellin, M. D.; Moran, A.; Wilhelm, J. J.; O'Brien, T. D.; Gottlieb, P. A.; Yu, L.; Dunn, T. B.
<x xml:space="preserve">Abstract</x> Total pancreatectomy with islet autotransplantation (TPIAT) is performed for definitive treatment of chronic pancreatitis; patients are not diabetic before surgery, or have C‐peptide positive pancreatogenous diabetes. Thus, TPIAT recipients are not traditionally considered at risk for autoimmune loss of the islet graft. We describe a 43‐year‐old female who underwent TPIAT with high mass islet graft of 6031 IEQ/kg, with no evidence of presurgical β cell autoimmunity who developed type 1 diabetes within the first year after TPIAT, resulting in complete loss of beta cell function. The patient had positive GAD and insulin autoantibodies at 1 year and 18 months after TPIAT, not present prior, and undetectable C‐peptide after mixed meal and intravenous glucose tolerance testing at 18 months. Glucagon secretion was preserved, suggesting the transplanted alpha cell mass was intact. HLA typing revealed a DR3/DR4 class II haplotype. This case highlights the need to consider de novo type 1 diabetes in patients with unexpected islet graft failure after TPIAT.